Feeding a diet devoid of choline to lactating rodents restricts growth and lymphocyte development in offspring. Issue 6 (2nd August 2016) - Lewis, E. D.; Goruk, S.; Richard, C.; Dellschaft, N. S.; Curtis, J. M.; Jacobs, R. L.; Field, C. J.
Abstract: The nutrient choline is necessary for membrane synthesis and methyl donation, with increased requirements during lactation. The majority of immune development occurs postnatally, but the importance of choline supply for immune development during this critical period is unknown. The objective of this study was to determine the importance of maternal supply of choline during suckling on immune function in their offspring among rodents. At parturition, Sprague–Dawley dams were randomised to either a choline-devoid (ChD; n 7) or choline-sufficient (ChS, 1 g/kg choline; n 10) diet with their offspring euthanised at 3 weeks of age. In a second experiment, offspring were weaned to a ChS diet until 10 weeks of age (ChD-ChS, n 5 and ChS-ChS, n 9). Splenocytes were isolated, and parameters of immune function were measured. The ChD offspring received less choline in breast milk and had lower final body and organ weight compared with ChS offspring ( P <0·05), but this effect disappeared by week 10 with choline supplementation from weaning. ChD offspring had a higher proportion of T cells expressing activation markers (CD71 or CD28) and a lower proportion of total B cells (CD45RA+) and responded less to T cell stimulation (lower stimulation index and less IFN- γ production) ex vivo ( P <0·05). ChD-ChS offspring had a lower proportion of total and activated CD4+ T cells, and produced less IL-6 after mitogen stimulation compared with cells from ChS-ChS ( P <0·05). Our study suggests that choline is required in the suckling diet to facilitate immune development, and choline deprivation during this critical period has lasting effects on T cell function later in life.